A Comprehensive Review on the Neuropharmacological Effects of Antidepressants in Various Prospects - Varshney, Sandesh; Alam, Md. Aftab; Kaur, Awaneet; Sharma, Shaweta (Current Psychopharmacology, 2024)
Depression is one of the most challenging diseases for society to treat. It is a highly prevalent and disabling illness in the general population. Affective disorders are characterised by depressed mood, diminished interest and pleasure, feelings of guilt or poor self-worth, sleep or food difficulties, decreased energy, and impaired attention. This manuscript will look at depression from a behavioural analytic perspective. The pathogenesis of major depressive disorder is poorly understood. Several lines of experimental and clinical evidence, however, show that the therapeutic effect of most antidepressant drugs is related to an increase in 5-HT-mediated neurotransmission. Alternative techniques, however, are employed to obtain this net effect. A better understanding of the neurological mechanism underpinning antidepressant drugs' delayed onset of action has resulted in the development of ways to accelerate antidepressant responses, which are discussed further below. Many antidepressant medications on the market today are beneficial, but they come with many downsides, including unpleasant side effects, potential interactions, and a low response rate. Natural drugs, on the other hand, are extremely effective, have a low risk, and a limited amount of side effects, which are covered briefly in this paper. Alternative modalities of administration have received a lot of attention in recent decades as a complement to approved prescription pharmaceuticals, especially for people who cannot tolerate oral or parenteral methods. The most promising non-invasive systemic delivery techniques are transdermal and transbronchial administration, and these are the focus of this research.
Keywords: transdermal